2021
DOI: 10.3390/plants10122819
|View full text |Cite
|
Sign up to set email alerts
|

The Patterns of Male and Female Flowers in Flowering Stage May Not Be Optimal Resource Allocation for Fruit and Seed Growth

Abstract: Changes in the proportions of male and female flowers in monoecious plants in response to external environmental conditions are directly related to the reproductive fitness of plants. The monoecious cucumber (Cucumber sativus) plant was used in this study to assess the responses of sex differentiation and the breeding process to nutrient supply and the degree of artificial pollination using pollen solutions of different concentrations. We found that the nutrient supply significantly improved the number of fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…On the other hand, as expected, the addition of fertilizers improves some vegetative (i.e., plant height, number of leaves, leaf area), floral (i.e., number of flowers, flower size), and reproductive traits (i.e., fruit set, number of seeds). Given that monoecious plants, such as squash, possess unisexual flowers, the effects of the addition of fertilizer may be different for the male and female function (Goldman and Willson, 1986;Dorken and Barrett, 2004;Hoover et al, 2012;Campbell et al, 2013;Li et al, 2020;Gao et al, 2021). For instance, the increase in the number of seeds may result from an increase in allocating resources from fertilizers to female function (Campbell and Halama, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, as expected, the addition of fertilizers improves some vegetative (i.e., plant height, number of leaves, leaf area), floral (i.e., number of flowers, flower size), and reproductive traits (i.e., fruit set, number of seeds). Given that monoecious plants, such as squash, possess unisexual flowers, the effects of the addition of fertilizer may be different for the male and female function (Goldman and Willson, 1986;Dorken and Barrett, 2004;Hoover et al, 2012;Campbell et al, 2013;Li et al, 2020;Gao et al, 2021). For instance, the increase in the number of seeds may result from an increase in allocating resources from fertilizers to female function (Campbell and Halama, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, different studies have shown that the input of nutrients into the soil increase the production and size of flowers, lengthen the flowering period, and improve the quality and quantity of nectar (Lau and Stephenson, 1993;Gardener and Gillman, 2001;Muñoz et al, 2005;Burkle and Irwin, 2010;Hoover et al, 2012;Gao et al, 2021). Given that pollinators show a greater preference for plants that have a greater floral display (Mitchell et al, 2004;Akter and Klecǩa, 2022), larger flowers (Conner and Rush, 1996) or flowers with better quality in rewards (Cnaani et al, 2006); the addition of soil fertilizers should benefit the interaction of plants with their pollinators, and thus, their reproductive success (Campbell and Halama, 1993;Hoover et al, 2012;Fernandez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…When fully developed, these fruits have a cylindrical shape with a length of 60 centimeters and a width of 10 centimeters. The color of the fruit matures from green to yellow as it age (Gao et al, 2021;Usha et al, 2015). Cucumber fruits comprise 95 percent water, 4% carbohydrate, and 1% protein.…”
Section: Nomenclature and Taxonomymentioning
confidence: 99%
“…This increase is expected to be directly proportional to the production of the plant. Gao et al [ 6 ] also stated that the number of female flowers has a positive correlation with the number of fruits per plant, while Bajaj et al [ 7 ] revealed that an increment led to higher fruit yield. The administration of ethephon can help increase the amount of natural pigments in fruits.…”
Section: Introductionmentioning
confidence: 99%